The Role Of Islamic Counseling Management In Increasing Learning Motivation Through Self-Confidence In Broken Home Family Students At Smk Negeri 1 Pringapus, Semarang District - Syafi’i Syafi’i; Hendrajaya Hendrajaya; Soehari Soehari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research was conducted at SMK Negeri 1 Pringapus with the research objectives being: (1) to describe the role of Islamic Guidance and Counseling management in increasing learning motivation through self-confidence, and (2) to describe the supporting and inhibiting factors for services in increasing learning motivation through self-confidence of students from broken home families.The type of research in this thesis is case study research in qualitative research. In collecting data, the methods used were (1) observation, (2) interviews, (3) documentation, and (4) primary and secondary data. In analyzing, research data uses qualitative analysis with steps for presenting data, reducing data, and drawing conclusions. The research results show that: (1) the implementation of Islamic Counseling Guidance at SMKN 1 Pringapus is still not optimal, because the ratio of the number of students and supervising teachers exceeds the standard, so that implementing the service is less effective; (2) some students' learning motivation and self-confidence are still low in the medium category, and a small number are in the high category; (3) services used to increase learning motivation and self-confidence for broken home students are group and individual counseling services; (4) supporting factors in implementing services are good cooperation between counseling teachers, homeroom teachers, PAI subject teachers, extracurricular coaches; and (5) the inhibiting factor in implementing services is that students are closed to communicating, so that supervising teachers have difficulty taking action that is appropriate to the student's condition and some subject teachers do not support the actions carried out by supervising teachers, because it disrupts lesson hours and the implementation time is less effective because have to wait for free time.